μ‐Opioid receptors in primary sensory neurons are essential for opioid analgesic effect on acute and inflammatory pain and opioid‐induced hyperalgesia - Sun, Jie; Chen, Shao‐Rui; Chen, Hong; Pan, Hui‐Lin (The Journal of physiology, 2019)
Key points μ‐Opioid receptors (MORs) are expressed peripherally and centrally, but the loci of MORs responsible for clinically relevant opioid analgesia are uncertain. Crossing Oprm1flox/flox and AdvillinCre/+ mice completely ablates MORs in dorsal root ganglion neurons and reduces the MOR expression level in the spinal cord. Presynaptic MORs expressed at primary afferent central terminals are essential for synaptic inhibition and potentiation of sensory input by opioids. MOR ablation in primary sensory neurons diminishes analgesic effects produced by systemic and intrathecal opioid agonists and abolishes chronic opioid treatment‐induced hyperalgesia. These findings demonstrate a critical role of MORs expressed in primary sensory neurons in opioid analgesia and suggest new strategies to increase the efficacy and reduce adverse effects of opioids. The pain and analgesic systems are complex, and the actions of systemically administered opioids may be mediated by simultaneous activation of μ‐opioid receptors (MORs, encoded by the Oprm1 gene) at multiple, interacting sites. The loci of MORs and circuits responsible for systemic opioid‐induced analgesia and hyperalgesia remain unclear. Previous studies using mice in which MORs are removed from Nav1.8‐ or TRPV1‐expressing neurons provided only an incomplete and erroneous view about the role of peripheral MORs in opioid actions in vivo. In the present study, we determined the specific role of MORs expressed in primary sensory neurons in the analgesic and hyperalgesic effects produced by systemic opioid administration. We generated Oprm1 conditional knockout (Oprm1‐cKO) mice in which MOR expression is completely deleted from dorsal root ganglion neurons and substantially reduced in the spinal cord, which was confirmed by immunoblotting and immunocytochemical labelling. Both opioid‐induced inhibition and potentiation of primary sensory input were abrogated in Oprm1‐cKO mice. Remarkably, systemically administered morphine potently inhibited acute thermal and mechanical nociception and persistent inflammatory pain in control mice but had little effect in Oprm1‐cKO mice. The analgesic effect of intrathecally administered morphine was also profoundly reduced in Oprm1‐cKO mice. Additionally, chronic morphine treatment‐induced hyperalgesia was absent in Oprm1‐cKO mice. Our findings directly challenge the notion that clinically relevant opioid analgesia is mediated mostly by centrally expressed MORs. MORs in primary sensory neurons, particularly those expressed presynaptically at the first sensory synapse in the spinal cord, are crucial for both opioid analgesia and opioid‐induced hyperalgesia. Key points μ‐Opioid receptors (MORs) are expressed peripherally and centrally, but the loci of MORs responsible for clinically relevant opioid analgesia are uncertain. Crossing Oprm1flox/flox and AdvillinCre/+ mice completely ablates MORs in dorsal root ganglion neurons and reduces the MOR expression level in the spinal cord. Presynaptic MORs expressed at primary afferent central terminals are essential for synaptic inhibition and potentiation of sensory input by opioids. MOR ablation in primary sensory neurons diminishes analgesic effects produced by systemic and intrathecal opioid agonists and abolishes chronic opioid treatment‐induced hyperalgesia. These findings demonstrate a critical role of MORs expressed in primary sensory neurons in opioid analgesia and suggest new strategies to increase the efficacy and reduce adverse effects of opioids.